2021
DOI: 10.3390/toxins13020124
|View full text |Cite
|
Sign up to set email alerts
|

Electric Blue: Molecular Evolution of Three-Finger Toxins in the Long-Glanded Coral Snake Species Calliophis bivirgatus

Abstract: The genus Calliophis is the most basal branch of the family Elapidae and several species in it have developed highly elongated venom glands. Recent research has shown that C. bivirgatus has evolved a seemingly unique toxin (calliotoxin) that produces spastic paralysis in their prey by acting on the voltage-gated sodium (NaV) channels. We assembled a transcriptome from C. bivirgatus to investigate the molecular characteristics of these toxins and the venom as a whole. We find strong confirmation that this genus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 98 publications
2
20
0
Order By: Relevance
“…These are non-enzymatic polypeptides with molecular weights of approximately 6-9 kDa, orientated in three beta-stranded loops that resemble three protruding fingers [ 50 , 51 ]. Comparison of the venom gland transcriptomic profiles between the current study and a recent report [ 17 ] reveals a similar dominating pattern of 3FTx, notwithstanding variation in the relative proportions of many toxin subtypes ( Table 3 ). The variation implies potential inter-individual differences between the specimens, e.g., wild versus captive snakes from different geographical regions, or extensive post-translational modifications [ 52 ].…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…These are non-enzymatic polypeptides with molecular weights of approximately 6-9 kDa, orientated in three beta-stranded loops that resemble three protruding fingers [ 50 , 51 ]. Comparison of the venom gland transcriptomic profiles between the current study and a recent report [ 17 ] reveals a similar dominating pattern of 3FTx, notwithstanding variation in the relative proportions of many toxin subtypes ( Table 3 ). The variation implies potential inter-individual differences between the specimens, e.g., wild versus captive snakes from different geographical regions, or extensive post-translational modifications [ 52 ].…”
Section: Resultssupporting
confidence: 80%
“…In the venom gland transcriptome, Cb_FTX01 and Cb_FTX02 were the two most abundantly expressed transcripts of S-3FTx. Both transcripts were annotated as calliotoxins (UniProtKB: P0DL82 and Cbivi_3FTx_034 reported by Dashevsky et al [ 17 ]), which is by far the only delta-neurotoxin discovered from snake venoms [ 10 ]. To elucidate variation in the genes, sequences of Cb_FTX01 and Cb_FTX02 were further compared with calliotoxins and representative alpha-neurotoxins from common elapid species found in Southeast Asia ( Figure 4 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One paper focuses on the molecular evolution of three-finger toxins (3FTX) in the snake genus Calliophis, which is the most basal branch of the family Elapidae [5]. It is shown that this genus produces the classic elapid eight-cysteine 3FTXs, which form several different clades.…”
mentioning
confidence: 99%